Phoenician in Greek Classical Sources (The study of the nature information about Phoenician according to Homerous and Herodotus) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The cities of the Canaanite civilization flourished on the eastern coast of the Mediterranean, and its centers extended from the Iskenderun region in northern Syria to Palestine, and it was famous for its cities: Ugarit, Arwad, Jbeil, Beirut, Tyre, Jericho, Acre and Gaza as major cities, with the presence of other smaller civilized centers. Part of this civilization has been spread in Syria and Lebanon. For example, the archaeological discovery of the centers of the Canaanite civilization, but the archaeological data provided by the discovered cities on the level of human civilization were very important, and it is an issue that raises the need for archaeological excavations, and the beginning of the historical Canaanite presence in its Syrian cultural and civilizational milieu. And if the Canaanite civilization left in its mother land, Syria, many achievements and cultural and cultural data, which is a rich field for historical and archaeological studies, but its cultural and civilizational radiation was not limited to the Syrian land, as it spread throughout the known ancient world, specifically in the West, where The Greeks knew it at the beginning of their civilization, and they called the Canaanites the name of the Phoenicians and their civilization, the Phoenician civilization, where their oldest historical and written sources spoke about the Canaanites, and provided a lot of important information about the Canaanite civilization. Hence, looking at the information related to the information contained in the original (Greek) sources, shedding light on it, and dealing with it with a scientific methodology to clarify it and present it to researchers and postgraduate students to benefit from it in its history and archaeology.